Changes in the Hepatic Artery Resistive Index After A Meal and Hypertension in Pregnancy: Case Report - Almeida, Monica Gomes de; Lauriano, Andre Guayanaz; Sa, Renato Augusto Moreira de (Cardiology and Cardiovascular Medicine, 2019)
In liver disease, the hepatic artery resistive index while fasting is higher, and there is less postprandial increase than in healthy subjects. The liver is one of the many organs that may be affected by endothelial dysfunction, vasospasm and ischemia that occur in pre-eclampsia. We report ten cases with hepatic artery resistive index (RI) variations in normotensive and hypertensive pregnant women. There was an increase in the RI in normotensive women and a reduction in hypertensive women after a mixed meal and an increase in the RI of more than 10% among normotensive women who ingested glucose. It is feasible to use any of the solutions during pregnancy. However, the 75 g glucose solution has greater potential for clinical application because it is routinely used in the prenatal period to screen for gestational diabetes. The incorporation of Doppler velocimetry of the hepatic artery in prenatal care, combined with screening for diabetes mellitus, would provide a low-cost alternative for predicting the unfavorable progression of hypertension, which would be especially valuable in places with limited resources. New studies may confirm the hypothesis raised in this case report that, as occurs in other causes of liver disease, a lower variation in the postprandial RI is associated with a higher probability of an unfavorable pregnancy outcome in hypertensive patients.